The effectiveness of the cooperative problem-based learning in improving the elementary school students’ critical thinking skills and interpersonal intelligence - Khalis Amrullah; Suwarjo Suwarjo (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2018)
This research aims to find out the effect of the cooperative problem-based learning on the improvement of the critical thinking and interpersonal intelligence of the fifth-grade students. This research was a quasi-experiment with the pretest-posttest control group design. The subjects were all fifth-grade students of SDN Liang Anggang 1, Pandahan 1, and Pandahan 2, Bati-Bati District of South Kalimantan in the second semester of the academic year 2015/2016. Data collection techniques that used were test and scale technique. The test was used to find out the critical thinking and the scale were used to find out the interpersonal intelligence.The hypothesis was tested using t-test and MANOVA with 0.05 significant levels. The result of this research shows that the use of the cooperative problem-based learning model in natural science teaching is effective in improving critical thinking and interpersonal intelligence of the fifth-grade students. Based on the result of t-test in posttest, the experimental I and II with control group show that the sig. 0.05 and the result of the MANOVA in the experimental I and II with control group show that the significant value 0.000 ˂ 0.05.